THE IMPLEMENTATION OF LINE WEBTOON TO ENHANCE STUDENTS’ READING COMPREHENSION - Retnoningrum, Jasmine Aryanti; Usman, Sriati; Dewi, Anjar Kusuma; Aminah, Aminah (Tadulako University, 2024)
This research aims to determine whether or not the implementation of Line Webtoon can enhance the reading comprehension of the eight grade students of SMP Negeri 4 Palu. The population of this research is the eighth-grade students of SMP Negeri 4 Palu. The sample was VIII A as the experimental class and VIII B as the control class. The research applied the quantitative method. The instrument of the data collection was pre-test and post-test. Those data were analyzed statistically. The pre-test was at a low level, and the post-test was at a high level. The pre-test was low because the students had difficulties in reading comprehension. However, the post-test that at a high level because of the media can enhance students’ reading comprehension. The results of the data analysis show that the t-counted was greater than the t-table. In conclusion, using line webtoon can enhance students’ reading comprehension.